P99 Relation of donor risk index and model for end-stage liver disease score to outcome of elective liver transplantation; a single centre experience. (16th November 2010) - Al-Freah, M; Al-Freah, M A B; Dionigi, E; Suddle, A; Aluvihare, V; Agarwal, K; Wendon, J; Auzinger, G; O'Grady, J; Rela, M; Heneghan, M; Heaton, N; et al.
Abstract : Introduction: Patients with advanced liver disease, reflected in high model for end-stage liver disease (MELD) scores have the lowest chances of survival without liver transplantation (LT) and yet, may derive greatest survival-benefit from LT. The use of extended criteria (EC) grafts in such patients has been advocated as a means of optimising the chances of successful transplantation. Aim: To determine the effects of graft quality (using Donor Risk Index, DRI) and MELD score at the time of LT on the duration of post-LT intensive care unit (ICU) and hospital length of stay (LOS) and survival. Method: Retrospective analysis of 898 adult patients who underwent elective LT (109 re-do LT) over the period 2000–2008. Pre-LT MELD scores were categorised as low (<15), intermediate (15–25), or High (>25). Graft quality was categorised as low (DRI >1.7) or High (DRI <1.7). Data are presented as median (IQR). Results: Median age was 53 years (44–60) and 64% were male. Median pre-LT MELD was 15 (11–19) and median DRI in the high and low quality groups were 1.5 (1.3–1.6) and 2.0 (1.9–2.1). Increasing MELD score was associated with greater ICU and Hospital LOS (p<0.0001, Kruskal–Wallis test). However, within each MELD category there was no significant difference in ICU or hospital LOS between recipients of grafts with DRI < or >1.7. See Abstract P99 table 1 . On multivariate regression analysis MELD was an independent predictor of LOS with no significant effect of DRI identified. Survival at 1-year in the overall cohort was 90%; in MELD <15 92.6%, 15–25 87.4% and >25 82.7%. There were no significant differences in 1 year survival between recipients with DRI < or >1.7 in the group as a whole or in the MELD sub-categories. Conclusion: In this cohort, length of ICU and hospital stay related to pre-LT MELD score and not graft quality as evaluated by DRI. Hospital and ICU stay and consequently resource use was increased particularly in those patients with MELD of 25 and above, but not further prolonged by the use of ECD grafts in the range of DRI used in this cohort.